1997
DOI: 10.1146/annurev.pharmtox.37.1.53
|View full text |Cite
|
Sign up to set email alerts
|

TISSUE RENIN-ANGIOTENSIN SYSTEM:A Site of Drug Action?

Abstract: In this review, we present background material that provides partial support for a tissue renin-angiotensin system (RAS). Evidence for the existence of this system relied in part on the use of drugs, which has entailed using low doses or concentrations of angiotensin-converting enzyme inhibitors, renin inhibitors, and angiotensin antagonists to block the RAS in vascular beds and in isolated arteries or organs. Other evidence for a tissue RAS has depended upon measurements of the components of the system, i.e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 87 publications
0
23
0
3
Order By: Relevance
“…This gives rise to the possibility that drugs acting on tissue RAS might ameliorate some of these disorders. In fact, a recent study has suggested functional consequences of the action of drugs on tissue RAS (Zimmerman & Dunham 1997).…”
Section: Circulating and Tissue Rasmentioning
confidence: 99%
“…This gives rise to the possibility that drugs acting on tissue RAS might ameliorate some of these disorders. In fact, a recent study has suggested functional consequences of the action of drugs on tissue RAS (Zimmerman & Dunham 1997).…”
Section: Circulating and Tissue Rasmentioning
confidence: 99%
“…Furthermore, ACE inhibitors reduce urinary protein excretion in renal disease and exert a longterm renoprotective effect (Ritz et al, 2000;Taal and Brenner, 2000), despite the incomplete antiproteinuric effect that only reaches an average of approximately 50% (Lees et al, 1990). Both systemic and local ACE inhibition are likely to contribute to the beneficial effect of ACE inhibitors, although their relative contributions remain an object of study (Anderson, 1997;Zimmerman and Dunham, 1997;Fogo, 2001). Drug targeting of an ACE inhibitor to the kidney can be an interesting approach to gain insight into the role of the local ACE in renal (patho)physiology.…”
mentioning
confidence: 99%
“…Exposure to maternal low protein diet in utero induces IUGR and increases expression of glomerular AT1 receptors and reduces AT2 receptor expression in young rat (Battista et al, 2002;Sahajpal & Ashton, 2005). A low protein diet of the mother is associated with lower birth weight and higher blood pressure in offspring, due to the suppression of renin mRNA and the decrease in the angiotensin II levels in the newborn rat kidney (Woods et al, 2001;Zimmerman & Dunham, 1997).…”
Section: Effects Of the Maternal Renal Dysfunction On The Fetusmentioning
confidence: 99%